Rancang Bangun Alat Pengering Eceng Gondok Untuk Bahan Kerajinan Tangan (Menggunakan Metode Tuning Controller Chien Regulator I dan Chien Servo I) - Aqidah Ahya Nurlaily; Irianto Irianto; Epyk Sunarno (Jurnal Teknologi dan Manajemen Informatika, 2017)
Hyacinth is a plant that can be utilized for the manufacture of various types of handicrafts, such as bags, sandals, souvenirs, and other furniture that has high art. In the process of making hyacinth crafts, it is considered in the process of drying. During this time, the hyacinth drying process still using conventional methods, which use solar energy which is dependent on weather conditions. Conventional drying methods relatively need long time, ie 7-10 days. So, that was designed hyacinth dryer that is not dependent on the weather and can be controlled with temperature sensors and weight sensor depend its set point. Hyacinth dryers use heater, blower and air circulation fan. The controller of the drying machine is Microcontroller ATMega 16 with PI Controll methods Tuning Controller Chien Regulator I with Kp = 4,55 and Ki = 0,3 and Tuning Controller Chien Servo I Kp = 2,65 and Ki = 0,156. Hyacinth drying with a dryer need time shorter than using the conventional drying method, ie 12 hours with stabil temperature 60ᵒC . With this dryer can dry 30 stems of hyacinth with initial weight 500g become dry hyacinth with weight ± 60g. Depends on the result of laboratory test, hyacint with dryer produce fiber content, water content, and ash content  that good enough.